2023
DOI: 10.3390/ijms24076371
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p53-Mediated Host–Virus Interaction in Coronavirus Infection

Abstract: The emergence of the SARS-CoV-2 coronavirus has garnered global attention due to its highly pathogenic nature and the resulting health crisis and economic burden. Although drugs such as Remdesivir have been considered a potential cure by targeting the virus on its RNA polymerase, the high mutation rate and unique 3’ to 5’ exonuclease with proofreading function make it challenging to develop effective anti-coronavirus drugs. As a result, there is an increasing focus on host–virus interactions because coronaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…The other 11 variants on chromosome 6, instead, mapped in the PERP gene locus and some of them were already annotated as eQTLs of this gene. Although no functions related to COVID-19 have been reported for the PERP gene, so far, it encodes a protein that is a p53 apoptosis effector, and, recently, Wang and colleagues reviewed the possible roles of p53 in mediating host-virus interactions in infections caused by Coronaviruses 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The other 11 variants on chromosome 6, instead, mapped in the PERP gene locus and some of them were already annotated as eQTLs of this gene. Although no functions related to COVID-19 have been reported for the PERP gene, so far, it encodes a protein that is a p53 apoptosis effector, and, recently, Wang and colleagues reviewed the possible roles of p53 in mediating host-virus interactions in infections caused by Coronaviruses 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It can also be a target for RNA viruses; for example, p53 is mislocalized to the cytoplasm by the NS2 protein during hepatitis C virus (HCV) infection [149]. However, only limited information is available on the relationship between SARS-CoV-2 and p53 (reviewed in [150]). It has been shown that the viral protease Nsp5 can act as a repressor of the p53 signalling pathway and that p53 can restrict SARS-CoV-2 production [151].…”
Section: Cell Cycle Regulation By Sars-cov-2mentioning
confidence: 99%